THE IMPACT OF PHYSICAL ACTIVITY IN THE HEALTH AND ECONOMIC SECTOR ON FORMAL SECTOR WORKERS: LITERATURE REVIEW - Saputra, Adi; Duana, I Made Kerta (ASEAN Journal of Sport for Development and Peace, 2023)
Non-Communicable Diseases (NCDs) account for 74% of all major deaths worldwide. The characteristics of the work with the highest prevalence of NCDs are experienced by formal sector workers. The risk factor for NCD with the highest number in the group of formal workers is low physical activity. This study aimed to compare the impact arising from the intensity of physical activity on formal sector workers in the health and economic sectors based on previous studies. This study employed the method of literature review. The research population includes all articles published in accredited national and international journals between 2018 and 2023 on the impact of physical activity in the health and economic sectors on formal sector workers or office workers. The research sample consists of 11 articles chosen based on inclusion criteria determined by searching the Google Scholar, Pubmed, and Garuda databases. Articles were selected for their suitability of title, full text, and discussion of the impact of physical activity on formal workers. Physical activity has been shown to reduce the risk of metabolic syndrome, hypertension, and lower back pain. Physical activity can also help workers' mental health. Several studies have found that physical activity has no effect on body fitness, risk of coronary heart disease, or worker productivity in the economy. Increasing physical activity in the formal sector, particularly at moderate to severe intensity, has a positive impact on workers' health. There was no significant impact of physical activity on economic improvements.